Early Cretaceous transpressional and transtensional tectonics straddling the Sulu orogenic belt, East China - Jun Wang (Geoscience Frontiers, 2019)
The Sulu orogenic belt (SOB) separates the North and South China blocks in East Asia and formed during Triassic continent-continent collision. However, late Mesozoic post-collisional exhumation is poorly understood due to lack of surface evidence for Paleo-Pacific subduction and associated effects. This paper interprets the tectonic history of the SOB using detrital zircon age data from Early Cretaceous sedimentary units along with previously published geochronologic and geochemical data to reconstruct sedimentological and tectonic history. Detrital zircon age distributions obtained from sedimentary units include a 2.0 Ga subpopulation that appears only in turbidite units to the southeast. This sediment probably derived from the Yangtze Block. Terrestrial facies from the Jiao-Lai basin to the northwest appear to derive from the North China Block. Geochronologic and geochemical data indicate that Early Cretaceous, post-collisional volcanism was compositionally bimodal (mafic-felsic) with associated intrusive activity that peaked at 120 Ma. Seismic images of northerly regions of the study area indicate this occurred in an extensional setting. Sedimentary facies and field structural analyses revealed an unconformity interpreted to reflect rapid uplift with NW–SE compression to the south. Given observed sinistral movement along the Tan-Lu fault, we interpret northwest and southeast regions of the SOB as experiencing transtensional and transpressional tectonics, respectively, driven by continuous subduction of the Paleo-Pacific Plate. Intrusion of the Late Yanshannian granitoids marked the final formational stage of this unique tectonic setting. Keywords: Detrital zircon, Seismic reflection, Structural analysis, Tectonic evolution, Early Cretaceous